Pain and somatic symptoms are sequelae of sexual assault: Results of a prospective longitudinal study. (10th September 2013) - Ulirsch, J.C.; Ballina, L.E.; Soward, A.C.; Rossi, C.; Hauda, W.; Holbrook, D.; Wheeler, R.; Foley, K.A.; Batts, J.; Collette, R.; Goodman, E.; McLean, S.A.
Abstract Background Cross‐sectional studies have shown that chronic musculoskeletal pain and somatic symptoms are frequently reported by sexual assault (SA) survivors; however, prospective studies examining pain and somatic symptoms in the months after SA have not been performed. Methods Women SA survivors 18 years of age or older who presented for care within 48 h of SA were recruited. Pain in eight body regions (head and face, neck, breast, arms, abdomen, back, genital and pelvic, and legs) and 21 common somatic symptoms (e.g., headache, nausea, insomnia, persistent fatigue) were assessed (0–10 numeric rating scale in each body region) at the time of presentation, 1‐week, 6‐week and 3‐month interview. Post‐traumatic stress disorder (PTSD) symptoms were assessed at the 6‐week and 3‐month interview. Results Clinically significant new or worsening pain (CSNWP) symptoms were common among study participants 6 weeks after SA [43/74, 58% (95% CI, 47–69%)] and 3 months after SA [40/67, 60% (95% CI, 48–71%)] and generally occurred in regions not experiencing trauma. Women SA survivors also experienced an increased burden of many common somatic symptoms: 8/21 (38%) and 11/21 (52%) common somatic symptoms showed a significant increase in severity 6 weeks and 3 months after SA, respectively. Correlations between PTSD, CSNWP and somatic symptoms were only low to moderate, suggesting that these outcomes are distinct. Conclusions New and/or clinically worsening pain and somatic symptoms, lasting at least 3 months, are sequelae of SA. Further studies investigating pain and somatic symptoms after SA are needed.